582 Changes on diastolic and atrial functions following a single bout of two different exercise modalities in patients with hypertension and ischaemic heart disease. (8th December 2021) - Caminiti, Giuseppe; Perrone, Marco; D'Antoni, Valentino; Morsella, Valentina; Catena, Marco; Cascelli, Giovanna; Iellamo, Ferdinando; Volterrani, Maurizio
Abstract: Aims: Concurrent aerobic plus resistance exercise (RAE) and high intensive interval exercise (HIIE) are both effective on inducing post-exercise hypotension (PEH) in patients with hypertension. However central haemodynamic changes associated to PEH in hypertensive subjects with underlying ischaemic heart disease (IHD) have been poorly investigated. To compare the acute effects produced by these two exercise modalities on left ventricular diastolic function and left atrial function. Methods and results: Twenty untrained male patients with history of hypertension and IHD under stable pharmacological therapy were enrolled. Each patient underwent three exercise sessions: RAE, HIIE, and a control session without exercise each lasting 45 min. Echocardiography examination was performed before and between 30 and 40 min from the end of the exercise sessions. In the first hour post exercise, BP values decreased in a similar way in RAE and HIIE and were unchanged after control. Compared to pre-session, E/E1 ratio increased after HIIE and remained unchanged after both RAE and control sessions (between-sessions P 0.002). PALS increased slightly after RAE (+1.4 ± 1.1%), decreased after HIIE (−4.6 ± 2.4%). and was unchanged after control. (between-sessions P 0.03). PACS was mildly increased after RAE, was reduced after HIIE, and was unchanged after control. Atrial volume was unchanged after both sessions. Left ventricular and left atrial stiffness increased significantly after HIEE while remained unchanged after RAE and control. Stroke volume and cardiac output increased after RAE, decreased after HIIE, and were unchanged after control. Conclusions: Single sessions of RAE and HIIE determined similar PEHs in hypertensive subjects with IHD, while they evoked different central haemodynamic adjustments. Given its neutral effects of on diastolic and atrial functions, RAE seems more suitable for reducing blood pressure in hypertensive patients with IHD.